2004
DOI: 10.1074/jbc.m309773200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the AMP-activated Protein Kinase Leads to Activation of Eukaryotic Elongation Factor 2 Kinase and to Its Phosphorylation at a Novel Site, Serine 398

Abstract: Protein synthesis consumes a high proportion of the metabolic energy of mammalian cells, and most of this is used by peptide chain elongation. An important regulator of energy supply and demand in eukaryotic cells is the AMP-activated protein kinase (AMPK). The rate of peptide chain elongation can be modulated through the phosphorylation of eukaryotic elongation factor (eEF) 2, which inhibits its activity and is catalyzed by a specific calcium/calmodulin-dependent protein kinase termed eEF2 kinase. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
269
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(287 citation statements)
references
References 35 publications
8
269
3
1
Order By: Relevance
“…Furthermore, pharmacological inducers of ER stress such as Tm and thapsigargin (Tg), an inhibitor of the ER-resident Ca 2 þ -dependent ATPase, induced eEF-2 phosphorylation with kinetics similar to those of sal (Supplementary Figure 3). EEF-2 phosphorylation has been observed in response to several stimuli, [26][27][28][29][30][31][32][33] but never in the context of ER stress. Our observations suggest that eEF-2 might be regulated by phosphorylation during ESR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, pharmacological inducers of ER stress such as Tm and thapsigargin (Tg), an inhibitor of the ER-resident Ca 2 þ -dependent ATPase, induced eEF-2 phosphorylation with kinetics similar to those of sal (Supplementary Figure 3). EEF-2 phosphorylation has been observed in response to several stimuli, [26][27][28][29][30][31][32][33] but never in the context of ER stress. Our observations suggest that eEF-2 might be regulated by phosphorylation during ESR.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] The phosphorylation of eEF-2 is catalyzed by eEF-2 kinase (eEF-2K), an unusual calcium/calmodulin-dependent enzyme belonging to the alpha kinase family of atypical protein kinases. 25 EEF-2 phosphorylation has been shown to play an important role in coupling protein synthesis to energy metabolism in response to calcium flux, 26 cyclic adenosine monophosphate (AMP)/protein kinase A and AMP-activated protein kinase signaling, [27][28][29][30] amino acid or glucose limitation, 31,32 and cytoplasmic pH changes, 33 but no role for eEF-2 phosphorylation in ER stress has been reported.…”
mentioning
confidence: 99%
“…input signal), this mechanism provides for exquisite control of eEF-2K output. To date, the molecular mechanisms underlying the activation of eEF-2K by PKA (32,54) and AMPK (55), which phosphorylate Ser-500 and Ser-398, respectively, are unknown. We believe this study provides a mechanistic foundation for the elucidation of these mechanisms.…”
Section: A Potential Conformational Transition Of the R-loop Promotesmentioning
confidence: 99%
“…Both AMPK and mTOR have been shown to phosphorylate eEF2 kinase, which leads to subsequent phosphorylation of the elongation factor eEF2 and inhibition in translation elongation (76,77). Liu et al showed that activation of AMPK during hypoxia resulted in strong eEF2 phosphorylation.…”
Section: Ampk-and Redd1-dependent Signaling To Mtor Through Tuberous mentioning
confidence: 99%